Burden of pemphigus vulgaris with a particular focus on women: A review. Issue 3 (3rd October 2022) - Kianfar, Nika; Dasdar, Shayan; Mahmoudi, Hamidreza; Daneshpazhooh, Maryam
Abstract : Pemphigus vulgaris is a chronic autoimmune mucocutaneous blistering disorder. Apart from the disease itself, other aspects of patients' life, including psychological, social, and financial, can be affected. Women are particularly more disposed to the impact of the disease due to their physiological characteristics, the specific periods of pregnancy and lactation as well as their social and familial role. In this review, we summarized the burden of pemphigus vulgaris on various aspects of women's lives. It is essential to understand these problems and provide appropriate support for patients with such a burdensome disease.